COMBINATION OF REGENERATIVE THERAPY AND FREE GINGIVAL GRAFT IN STAGE IV PERIODONTITIS: CASE REPORT - Resky Ramadhani; Ayu Rahayu Feblina; Dian Setiawati (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Periodontal regenerative therapy can be used to repair damaged periodontal tissues caused by periodontitis. The combination of regenerative periodontal surgery and FGG (Free Gingival Graft) is expected to accelerate the regeneration of periodontal tissue. Case : A 37-year-old woman came with complaints of loose lower front teeth, frequent bleeding and pain when eating and drinking. The complaint was felt since 1 year ago. Clinical examination obtained an average pocket depth of 6 mm and an average second degree of tooth mobility. On radiographic examination found bone damage horizontally. Case Management: The patient received root planing scaling and occlusion adjustment, followed by dental periodontal surgery 42,41,31,32. Stage II surgery for recession closure therapy with FGG was carried out three months after stage 1 surgery was performed. Discussion: Regenerative periodontal surgery is performed to produce new periodontal tissue growth and restore connective tissue attachment to the teeth. Free Gingival Graft is performed to increase gingival keratinization and improve patient esthetics. Conclusion and Suggestions: The combination of regenerative periodontal surgery and FGG for the treatment of periodontitis cases involving severe bone destruction gives good results of periodontal tissue healing by alveolar bone healing and regeneration and quite good aesthetics.